Humanoid robot simulation with a joint trajectory optimized controller - Lima, José (2010)
This paper describes a joint trajectory optimized controller for a humanoid robot simulator following the real robot characteristics. As simulation is a powerful tool for speeding up the control software development, the proposed accurate simulator allows to fulfil this goal. The simulator, based on the Open Dynamics Engine and GLScene graphics library, provides instant visual feedback. The proposed simulator, with realistic dynamics, allows to design and test behaviours and control strategies without access to the real hardware in order to carry out research on robot control without damaging the real robot in the early stages of the development. The joints controller techniques, such as acceleration, speed and energy consumption minimization are discussed and experimental results are presented in order to validate the proposed simulator.